Informed Headquarters and Socialistic Internal Capital Markets - Hoang, Daniel; Ruckes, Martin (Review of Finance, 2015)
Abstract This article develops a theory of resource allocation in internal capital markets that is consistent with the empirical finding that multidivision firms bias their investment levels in favor of divisions with weaker investment prospects. Headquarters has private information about the capital productivities of its divisions; therefore, capital allocations in the present serve as a signal to divisional managers about future allocations. To facilitate effort provision, headquarters biases capital allocation so as to not disclose productivity differences across divisions or to credibly signal their absence. The capital allocation bias is time-varying and the relationship between the bias and the difference in average division productivities is inversely U-shaped.